2017
DOI: 10.1093/humupd/dmx017
|View full text |Cite
|
Sign up to set email alerts
|

GnRH antagonist versus long agonist protocols in IVF: a systematic review and meta-analysis accounting for patient type

Abstract: In a general IVF population, GnRH antagonists are associated with lower ongoing pregnancy rates when compared to long protocol agonists, but also with lower OHSS rates. Within this population, antagonist treatment prevents one case of OHSS in 40 patients but results in one less ongoing pregnancy out of every 28 women treated. Thus standard use of the long GnRH agonist treatment is perhaps still the approach of choice for prevention of premature luteinization. In couples with PCOS and poor responders, GnRH anta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
239
3
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 324 publications
(257 citation statements)
references
References 77 publications
10
239
3
5
Order By: Relevance
“…Subgroup analysis for the fixed antagonist protocol demonstrated no evidence with or without OCP (RR: 0.94, 95% CI: 0.79-1.12 and RR: 0.94, 95% CI: 0.83-1.05, respectively). Lastly, antagonist cycles resulted in statistically lower OHSS rates both in the overall IVF patients and in patients with PCOS (RR: 0.63, 95% CI: 0.50-0.81 and RR: 0.53, 95% CI: 0.30-0.95, respectively), with no data reported on patients with POR (Lambalk et al 2017).…”
Section: Stimulation Protocolmentioning
confidence: 90%
See 2 more Smart Citations
“…Subgroup analysis for the fixed antagonist protocol demonstrated no evidence with or without OCP (RR: 0.94, 95% CI: 0.79-1.12 and RR: 0.94, 95% CI: 0.83-1.05, respectively). Lastly, antagonist cycles resulted in statistically lower OHSS rates both in the overall IVF patients and in patients with PCOS (RR: 0.63, 95% CI: 0.50-0.81 and RR: 0.53, 95% CI: 0.30-0.95, respectively), with no data reported on patients with POR (Lambalk et al 2017).…”
Section: Stimulation Protocolmentioning
confidence: 90%
“…More recently, a systematic review and meta-analysis evaluated the effect of the type of GnRH analog used to prevent the endogenous LH surge, with special attention to differences in subset of patients and interventions (Lambalk et al 2017). Fifty studies were included, of which 34 studies reported on general IVF patients, 10 studies reported on polycystic ovary syndrome (PCOS) patients and 6 studies reported on POR (Lambalk et al 2017). In general IVF patients, ongoing PR was significantly lower in patients using an antagonist (RR: 0.89, 95% CI: 0.82-0.96).…”
Section: Stimulation Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…Although individualized FSH dosing has focused on the prevention of extreme ovarian responses, the increased use of a gonadotropin‐releasing hormone (GnRH) antagonist protocol has provided therapeutic options in case an actual hyper response occurs. The possibility of GnRH‐agonist triggering with or without freeze‐all strategy in such protocols seems to considerably reduce OHSS risks, but conflicting results have been revealed about their impact on LBR . Also, OHSS risks were not completely eliminated for all patients in the GnRH‐antagonist protocol, indicating that FSH dose reductions might still be needed.…”
Section: Discussionmentioning
confidence: 99%
“…As the number of oocytes retrieved has been observed to be positively correlated with pregnancy and live birth outcomes, COS should be the preferred treatment option in this population [12][13][14][15]. Meta-analyses have demonstrated that gonadotropinreleasing hormone (GnRH) agonists and antagonists have comparable efficacy; however, antagonist protocols are recommended because they offer improved safety owing to a lower risk for ovarian hyperstimulation syndrome (OHSS) [16][17][18][19][20][21][22]. The risk for OHSS is also reduced by the use of a GnRH agonist rather than human chorionic gonadotropin (hCG) to trigger ovulation and this can be considered for high responders [17].…”
Section: Ovulatory Women (Including Women With Unexplained Infertilitmentioning
confidence: 99%